2005
DOI: 10.1029/2004jb003445
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical remanent magnetization in Precambrian rocks: Are we sure the geomagnetic field was weak?

Abstract: [1] Thellier paleointensity determinations from two dikes of the Early Proterozoic ($2.46 Ga) Matachewan dike swarm (Canada) yield field values of 2.14 ± 0.18 and 9.81 ± 1.65 mT. Corresponding values of virtual axial dipole moment are very low (0.54 ± 0.05 Â 10 22 and 2.49 ± 0.42 Â 10 22 Am 2 , respectively) when compared with the modern field. The characteristic remanent magnetization (ChRM) was isolated over a narrow range of high unblocking temperatures ($520-580°C). Detailed rock magnetic analyses indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 92 publications
7
54
0
2
Order By: Relevance
“…The potential for biasing caused by the remanence carriers undergoing chemical changes below their Curie temperature during the original cooling of the unit (and therefore retaining a chemical or thermochemical remanence) is, as for many studies, not so well constrained. The nature of such effects and the extent to which they occur is presently an area of active research (Smirnov and Tarduno, 2005;Draeger et al, 2006;Yamamoto, 2006). Here, we merely point out that the results of the rock magnetic analysis are consistent with the units having acquired a purely thermal remanence.…”
Section: Discussionmentioning
confidence: 56%
“…The potential for biasing caused by the remanence carriers undergoing chemical changes below their Curie temperature during the original cooling of the unit (and therefore retaining a chemical or thermochemical remanence) is, as for many studies, not so well constrained. The nature of such effects and the extent to which they occur is presently an area of active research (Smirnov and Tarduno, 2005;Draeger et al, 2006;Yamamoto, 2006). Here, we merely point out that the results of the rock magnetic analysis are consistent with the units having acquired a purely thermal remanence.…”
Section: Discussionmentioning
confidence: 56%
“…The correct identification of magnetic mineralogy is crucial for absolute paleointensity interpretation (Smirnov and Tarduno, 2005). The samples selected for Thellier paleointensity experiments should necessarily carry primary TRM (thermoremanent magnetization).…”
Section: Resultsmentioning
confidence: 99%
“…SEM and low-temperature magnetic analyses indicated that these phases are nearly stoichiometric magnetite and ilmenite produced by oxyexsolution (Smirnov and Tarduno, 2005). The sample manifests PSD hysteresis behavior ( Fig.…”
Section: Dmentioning
confidence: 99%